Ear canal and middle-ear tumors: a single-institution series of 87 patients - Nicoli Taija K.; Atula Timo; Sinkkonen Saku T.; Korpi Jarkko; Vnencak Matej; Tarkkanen Jussi; Mäkitie Antti A.; Jero Jussi (Taylor & Francis (Commercial Publisher), 2022)
Background: Ear canal and middle ear tumors are rare and exhibit variability in histology and clinical manifestation. Surgical resection remains the treatment of choice, but individualized approach is needed to preserve function when possible.
Aims/objectives: To review the management and outcome of ear canal and middle ear tumors at an academic referral center.
Materials and methods: Helsinki University Hospital (HUS) patient files were searched for clinically and histologically confirmed ear canal and middle ear tumors over a 14-year period. The minimum follow-up time was 2 years.
Results: Eighty-seven patients with 88 tumors were identified. There were 20 (23%) benign external auditory canal (EAC), 36 (41%) benign middle ear space (MES), 29 (33%) malignant EAC, and 3 (3%) malignant MES tumors. Most (92%) tumors were managed with primary resection. Thirty-five percent of the operatively managed patients had a residual or a recurrent tumor.
Conclusions and significance: EAC and MES tumors show great diagnostic and histologic heterogeneity with need for individualized investigative and treatment approaches. In benign tumors, we advocate aggressive local surgical control without sacrificing vital structures. In malignant tumors, we recommend local surgical control with or without adjunct RT.